Doctor Who - Twelfth Night adventures in time and space with Peter Capaldi - O'Day, Andrew (I.B. Tauris, 2019)
Intro -- Contents -- List of Figures -- Contributors -- Note on Terminology -- Acknowledgements -- Introduction -- Part One: The Doctor and His Companions -- 1. A Young-Old Face: Out with the New and in with the Old in Doctor Who -- 2. 'I'm Scottish … I can really complain about things now': Discourses of Scotland and Scottishness in Doctor Who -- 3. Clara's Choice: The Political Lunarscape of 'Kill the Moon' -- Part Two: Further Politics and Themes -- 4. A Good Man Goes to War? The Twelfth Doctor and the Politics of Conflict -- 5. 'Chap with wings there, five rounds rapid': UNIT and the Politics of Doctor Who -- 6. Heaven Sent? The Afterlife, Immortality and Controversy in the Steven Moffat/Peter Capaldi Era -- 7. Comfort and Joy? The Steven Moffat/Peter Capaldi Christmas Specials -- Part Three: Promotional Discourses -- 8. 'Please welcome the Twelfth Doctor': The Paratextual Branding of Peter Capaldi's Tenure -- 9. The Transcultural Fan: Branding Series 8 of Doctor Who in the US -- Part Four: Fandom -- 10. 'Doctor Who belongs to all of us': Fan Texts and Fans' Imaginings of the Future Twelfth Doctor -- 11. Hit or Miss? Fan Responses to the Regenderation of the Master -- Appendix: Audience data -- List of Episodes: The Steven Moffat/Peter Capaldi era -- Index
Keywords: Doctor-(Fictitious character); Doctor Who (Television program : 2005- )